Spiritual reading : a study of the Christian practice of reading scripture - Harvey, Angela Lou; Moberly, R. W. L. (Cambridge, United Kingdom : James Clarke & Co., 2016)
"Reading Scripture is a spiritual practice at the very heart of the Christian faith. But how is it possible to encounter God in reading the words of the Bible? Does reading the Christian Bible require a different approach from how one may read other texts or writings? What is required of the spiritual reader to read well? Seeking to answer such questions, Angela Lou Harvey provides a theological exploration of the idea of "spiritual reading" in the context of the Western church today. Drawing upon insights of theologians such as Karl Barth, Henri de Lubac, and Ellen F. Davis, the author suggests that the particulars of Christian belief profoundly shape the distinctive practice of the spiritual reading of the Bible."--
Introduction -- Spiritual reading and the church -- Reading well -- Karl Barth and the reality of God in scripture -- Henri de Lubac and the spiritual sense of scripture -- An artful reader: Ellen F. Davis -- Ellen Davis's art in practice -- Conclusion.
Includes bibliographical references (pages 223-233).
PDF (JSTOR, viewed Apr. 24, 2017).
Keywords: Bible -- Reading; Bible -- Criticism, interpretation, etc; Barth, Karl, -- 1886-1968.; Lubac, Henri de, -- 1896-1991.; Davis, Ellen F; Spiritual life -- Christianity; Spiritual life -- Christianity; Bible - Reading; Barth, Karl, 1886-1968.; Lubac, Henri de, 1896-1991.; Bible - Criticism, Interpretation, etc; Davis, Ellen F; Reading; BIBLES / General; RELIGION / Biblical Reference / General; RELIGION / Biblical Reference / Handbooks; Criticism, interpretation, etc; Criticism, interpretation, etc; Electronic books